Risk Perception of COVID-19 Infection and Adherence to Preventive Measures among Adolescents and Young Adults - Xin Yu Yang; Rui Ning Gong; Samuel Sassine; Maxime Morsa; Alexandra Sonia Tchogna; Olivier Drouin; Nicholas Chadi; Prévost Jantchou (MDPI AG, 2020)
To explore factors influencing adolescents and young adults' (AYAs) risk perception of COVID-19 and adherence to public health measures, we conducted a cross-sectional online survey of AYAs (14-22 years old) from Quebec (Canada) recruited through school and community partners in April 2020 during the first wave of the COVID-19 pandemic. The study included 3037 participants (mean age = 17.7 years, 74.6% female). AYAs had higher mean (standard deviation (SD)) risk perception of COVID-19 for their relatives (8.2 (1.9)) than for themselves (5.6 (2.6)) (p < 0.001). Factors associated with higher risk perception included higher disease knowledge (adjusted odds ratio (aOR) 1.06, 95% CI 1.01-1.11), presence of chronic disease (aOR 2.31, 95%CI 1.82-2.93) and use of immunosuppressants (aOR 2.53, 95%CI 1.67-3.87). AYAs with a higher risk perception (aOR 1.06, 95%CI 1.02-1.10) those wishing to help flatten the disease curve (aOR 1.18, 95%CI 1.12-1.25) or to protect their family/friends (aOR 1.14, 95%CI 1.05-1.24) were more likely to engage in preventive behaviors. Self-perceived risk and desire to protect others were significantly associated with adherence to preventive measures among youth. These findings may help inform public health messaging to AYAs in the current and future pandemics.